FREQUENCY OF HCV INFECTION IN DIFFERENT DERMATOLOGICAL DISORDERS - Rahman, Atiya; Rizvi, Syed Dilawar Abbas; Sheikh, Zafar Iqbal (Journal of Ayub Medical College Abbottabad, 2012)
Background: Hepatitis C Virus (HCV) has estimated affected nearly 3% of the world population. Studies in Pakistan have shown a somewhat higher prevalence. The objective of this study was to determine the frequency of hepatitis C virus infection in patients with dermatological disorders, known to be associated with HCV infection. Method: This was a descriptive study, conducted at Departments of Dermatology, Military Hospital, Rawalpindi and PNS Shifa, Karachi from September 2003 to November 2005. There were 355 patients of the dermatologic disorders mentioned above. HCV status was determined by the presence of anti-HCV antibodies in the serum, by third generation ELISA. Results: In this study 14% of lichen planus, 8% of generalised pruritus, 7.8% of urticaria, 8.7% of prurigo, and 50% of porphyria cutanea tarda patients had underlying HCV infection. None of the patients of leukocytoclastic vasculitis, erythema multiforme or erythema nodosum had anti-HCV antibodies. No patient of mixed cryoglobulinaemia or polyarteritis nodosa was seen during the study period. Conclusions: Patients of lichen planus, generalised pruritus, urticaria, prurigo, and porphyria cutanea tarda have increased frequency of HCV infection compared to normal population of our country. In contrast, none of the patients of leukocytoclastic vasculitis, erythema multiforme or erythema nodosum had HCV infection. Keywords: HCV, cutaneous disorders, lichen planus, porphyria cutanea tarda, urticaria, pruritus, prurigo, erythema multiforme, erythema nodosum